Pengaruh Strategi Two Stay Two Stray dan Cooperative Integrated Reading and Composition Terhadap Hasil Belajar Matematika Ditinjau Dari Keaktifan Belajar Siswa kelas VIII di SMP Muhammadiyah 4 Surakarta Tahun 2015/2016 - Maharani Ainur, Citra; , Drs. Slamet H.W., M.Pd (2016)
The aims of this research were to know: (1) the influence of learning strategies Two Stay Two Stray and Cooperative Integrated Reading and Composition on mathematic learning outcomes, (2) the influence of students active learning on mathematic learning outcomes, and (3) the interaction between learning strategies with students active learning on mathematic learning outcomes. The kind of research is quantitative with quasi experimental design. The population in this research was all students of class VIII SMP Muhammadiyah 4 Surakarta year academic 2015/2016. The sample of this research consisted of two class, they were experiment class and controlled class. The sampling technique used cluster random sampling. The technique of collecting data used test, inquiry, and documentation. The technique of analysis data used two ways analysis of variance with unbalanced cells. The result of analyzing data with significant level 5% shows that: (1) there was influence of learning strategies Two Stay Two Stray and Cooperative Integrated Reading and Composition on mathematic learning outcomes, (2) there was influence of students active learning on mathematic learning outcomes, and (3) there was no interaction between learning strategies with students active learning on mathematic learning outcomes.